Effects of Ant (Formica subsericea) Nest Development on Physical and Hydrological Properties in a Coarse-Textured Soil. Issue 3 (March 2016) - Drager, Kim I.; Hirmas, Daniel R.; Hasiotis, Stephen T.; Bents, Timothy C.
Abstract : Abstract: Ants may compose a large portion of the total biomass in an ecosystem and can play a significant role in soil turnover and nutrient cycling. Monitoring ant nest architecture and growth in the field can be difficult because of the destructive nature of casting ant nests. To examine nest effects on soil hydrology during different stages of development, 828 Formica subsericea workers were placed in each of two large (1.0 × 1.0 × 0.1 m) formicaria and allowed to excavate for 82 days in a coarse-textured soil collected from the field. Photographs and transparencies were used to record nest structure for five different time steps during development. After the fifth time step on Day 82, the nest was cast with dental plaster and the formicarium media were sampled. The development of the nest was associated with an increase in saturated conductivity of the soil. Backfilled entrances and vertical galleries contributed to decreasing saturated conductivity as worker numbers declined toward the end of the experiment. The presence of nests was associated with an increase in water flux through the soil material, although the effect was not as dramatic as in soils with a naturally lower saturated hydraulic conductivity.